1994
DOI: 10.1021/bi00186a033
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Rabbit Muscle Pyruvate Kinase Complexed with Mn2+, K+, and Pyruvate

Abstract: The molecular structure of rabbit muscle pyruvate kinase, crystallized as a complex with Mn2+, K+, and pyruvate, has been solved to 2.9-A resolution. Crystals employed in the investigation belonged to the space group P1 and had unit cell dimensions a = 83.6 A, b = 109.9 A, c = 146.8 A, alpha = 94.9 degrees, beta = 93.6 degrees, and gamma = 112.3 degrees. There were two tetramers in the asymmetric unit. The structure was solved by molecular replacement, using as the search model the coordinates of the tetramer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
217
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(235 citation statements)
references
References 54 publications
16
217
1
1
Order By: Relevance
“…Analysis of the numerous X-ray diffraction data sets collected during structure determination has revealed that the B-domain varies its orientation from crystal to crystal, thereby causing non-isomorphism. In this respect, variability of the B domain orientation has been observed also in the cat [6] and rabbit [7] M1 PK structures, further emphasising the enzyme flexibility and modularity, two key properties which are at the heart of the regulatory mechanism. Moreover, these independent observations suggest that the T-and R-states probably represent, in PK, an ensemble of conformations rather than a single well defined structure.…”
Section: The Allosteric Transitionmentioning
confidence: 86%
“…Analysis of the numerous X-ray diffraction data sets collected during structure determination has revealed that the B-domain varies its orientation from crystal to crystal, thereby causing non-isomorphism. In this respect, variability of the B domain orientation has been observed also in the cat [6] and rabbit [7] M1 PK structures, further emphasising the enzyme flexibility and modularity, two key properties which are at the heart of the regulatory mechanism. Moreover, these independent observations suggest that the T-and R-states probably represent, in PK, an ensemble of conformations rather than a single well defined structure.…”
Section: The Allosteric Transitionmentioning
confidence: 86%
“…Interactions such as this, between the monovalent ion and a hydroxyl, seem to be unique to b-galactosidases. The functions of monovalent cations at the active sites of all other enzymes that are known to have monovalent metal requirements [44][45][46][47][48][49] either help neutralize the negative charge of substrate phosphate groups, often in conjunction with a divalent cation, or they have structural importance, but in this case, Na ĂŸ interacts with a hydroxyl group.…”
Section: Overview Of the Enzymatic Reactionmentioning
confidence: 99%
“…The highly conserved Ala154 is located close to active site residues Arg116 (involved in substrate binding [Valentini et al, 2002] and ATP/ADP binding [Larsen et al, 1994;Muirhead et al, 1986;Rigden et al, 1999]) and Asp156 (involved in K 1 binding [Jurica et al, 1998;Larsen et al, 1994;Rigden et al, 1999;Wooll et al, 2001]). The approximate 50% decrease in PK enzymatic activity as measured in the heterozygous Patient 24 indicates that substitution with threonine may perturb this interaction, thereby hampering catalysis.…”
Section: The Novel Pgly111arg Pk Variant Is Prevalent In the Dutch Pmentioning
confidence: 99%